Evolutions of microstructure, phase, microhardness, and residual stress of multiple laser shock peened Ni-based single crystal superalloy after short-term thermal exposure. (March 2020) - Geng, Yongxiang; Dong, Xia; Wang, Kedian; Mei, Xuesong; Tang, Zhanghan; Duan, Wenqiang
Highlights: [3 1 1] oriental Ni-based single crystal superalloy was treated by LSP. Slipping systems of {1 1 1} 〈1 1 0〉 were initiated by LSP in [3 1 1] orientation. Dislocation structures had a vital effect on the misfits of γ and γ′ phases. Abstract: In this work, evolutions of microstructure, phase, microhardness, and residual stress of multiple laser shock peened (LSP) Ni-based single crystal (SC) superalloy after short-term thermal exposure for 1 h at 950 °C and 1200 °C were investigated. The results showed that slipping systems of {1 1 1} 〈1 1 0〉 were activated by multiple LSP in [3 1 1] orientation, which resulted in the formation of dislocation slip bands along (1  1 ¯  1) plane. The dislocation structures induced by LSP in γ and γ′ phases had a vital influence on the lattice misfits of two phases as compared to the composition changes of γ phase, which led to increased lattice misfits. Moreover, the decrease in microhardness and residual stress after thermal exposure was attributed to the decrease in dislocation density due to dislocation annihilation.